Line × Tester Mating Design Analysis for Grain Yield and Yield Related Traits in Bread Wheat (Triticum aestivum L.) - Zine El Abidine Fellahi; Abderrahmane Hannachi; Hamenna Bouzerzour; Ammar Boutekrabt (International Journal of Agronomy)
Nine bread wheat (Triticum aestivum L.) genotypes were crossed in a line × tester mating design. The 20 F1's and their parents were evaluated in a randomized complete block design with three replications at the Field Crop Institute-Agricultural Experimental Station of Setif (Algeria) during the 2011/2012 cropping season. The results indicated that sufficient genetic variability was observed for all characters studied. A899 × Rmada, A899 × Wifak, and A1135 × Wifak hybrids had greater grain yield mean than the parents. A901 line and the tester Wifak were good combiners for the number of grains per spike. MD is a good combiner for 1000-kernel weight and number of fertile tillers. HD1220 is a good general combiner to reduce plant height; Rmada is a good general combiner to shorten the duration of the vegetative growth period. A901 × Wifak is a best specific combiner to reduce plant height, to increase 1000-kernel weight and number of grains per spike. AA × MD is a best specific combiner to reduce duration of the vegetative period, plant height and to increase the number of kernels per spike. A899 × Wifak showed the highest heterosis for grain yield, accompanied with positive heterosis for the number of fertile tillers and spike length, and negative heterosis for 1000-kernel weight and the number of days to heading. σgca2/σsca2,  (σD2/σA2)1/2 low ratios and low to intermediate estimates of h2ns supported the involvement of both additive and nonadditive gene effects. The preponderance of non-additive type of gene actions clearly indicated that selection of superior plants should be postponed to later generation.